Elucidating tumor heterogeneity from spatially resolved transcriptomics data by multi-view graph collaborative learning - Chunman Zuo; Yijian Zhang; Chen Cao; Jinwang Feng; Mingqi Jiao; Luonan Chen (Nature Communications, 2022)
Multi-view graph approaches could enhance the analysis of tissue heterogeneity in spatial transcriptomics. Here, the authors develop the Spatial Transcriptomics data analysis by Multiple View Collaborative-learning - stMVC - framework, and apply it to detect spatial domains and cell states in brain and tumor tissues.